Extracellular clusterin limits the uptake of α‐synuclein fibrils by murine and human astrocytes. Issue 3 (12th October 2020) - Filippini, Alice; Mutti, Veronica; Faustini, Gaia; Longhena, Francesca; Ramazzina, Ileana; Rizzi, Federica; Kaganovich, Alice; Roosen, Dorien A.; Landeck, Natalie; Duffy, Megan; Tessari, Isabella; Bono, Federica; et al.
Abstract: The progressive neuropathological damage seen in Parkinson's disease (PD) is thought to be related to the spreading of aggregated forms of α‐synuclein. Clearance of extracellular α‐synuclein released by degenerating neurons may be therefore a key mechanism to control the concentration of α‐synuclein in the extracellular space. Several molecular chaperones control misfolded protein accumulation in the extracellular compartment. Among these, clusterin, a glycoprotein associated with Alzheimer's disease, binds α‐synuclein aggregated species and is present in Lewy bodies, intraneuronal aggregates mainly composed by fibrillary α‐synuclein. In this study, using murine primary astrocytes with clusterin genetic deletion, human‐induced pluripotent stem cell (iPSC)‐derived astrocytes with clusterin silencing and two animal models relevant for PD we explore how clusterin affects the clearance of α‐synuclein aggregates by astrocytes. Our findings showed that astrocytes take up α‐synuclein preformed fibrils (pffs) through dynamin‐dependent endocytosis and that clusterin levels are modulated in the culture media of cells upon α‐synuclein pffs exposure. Specifically, we found that clusterin interacts with α‐synuclein pffs in the extracellular compartment and the clusterin/α‐synuclein complex can be internalized by astrocytes. Mechanistically, using clusterin knock‐out primary astrocytes and clusterin knock‐down hiPSC‐derived astrocytes we observed that clusterin limits the uptake of α‐synuclein pffs by cells. Interestingly, we detected increased levels of clusterin in the adeno‐associated virus‐ and the α‐synuclein pffs‐ injected mouse model, suggesting a crucial role of this chaperone in the pathogenesis of PD. Overall, our observations indicate that clusterin can limit the uptake of extracellular α‐synuclein aggregates by astrocytes and, hence, contribute to the spreading of Parkinson pathology. Main Points: Extracellular clusterin binds α‐synuclein fibrils thus limiting their uptake by murine and human astrocytes. Reduced levels of clusterin improve α‐synuclein aggregates clearance by astrocytes.